5‐Azacitidine Monotherapy Followed by Related Haploidentical Hematopoietic Stem Cell Transplantation Achieves Durable Remission in a Pediatric Patient With Acute Undifferentiated Leukemia Refractory to High‐Dose Chemotherapy. Issue 6 (23rd February 2016) - Polishchuk, Veronika; Khazal, Sajad; Berulava, Giorgi; Roth, Michael; Mahadeo, Kris M.
Abstract : Patients with acute leukemias of undifferentiated lineage (AUL) generally have guarded prognosis. Here, we describe the first reported pediatric patient with AUL refractory to high‐dose chemotherapy who achieved clinical remission with ALL maintenance therapy and 5‐azacitidine. His induction remission was followed by consolidation with reduced toxicity haploidentical hematopoietic stem cell transplant (HSCT). At 9 months post‐HSCT, the patient is alive and in remission. This combination therapy of remission induction with ALL maintenance therapy and 5‐azacitidine and consolidation with reduced toxicity haploidentical HSCT is novel and promising for patients who lack conventional donors and are not candidates for myeloablative therapy.